(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The formation of an academic rowing team crew is a multifaceted process that requires careful planning, coordination, and dedication. This scientific article explores the various aspects involved in creating and nurturing a successful academic rowing team crew. It delves into the recruitment, training, and management strategies necessary for developing a cohesive and competitive crew. Drawing from both scientific research and practical experience, this article provides valuable insights for universities and colleges aiming to establish or improve their rowing programs.